Troponin T levels associated with genetic variants in NOTCH2 and MTNR1B in women with psychosis. (April 2017) - Hukic, Dzana Sudic; Lavebratt, Catharina; Olsson, Eric; Östenson, Claes-Göran; Eriksson, Sven V.; Erlinge, David; Schalling, Martin; Ösby, Urban
Abstract: Psychosis patients have increased prevalence of metabolic disorders, which increase the risk for cardiovascular disease. Elevated troponin T level is an early biomarker of cardiovascular damage. We tested for association between troponin T levels and genetic risk variants of elevated blood glucose level in psychosis. Glucose and troponin T levels correlated positively. MTNR1B rs10830963 and NOTCH2 rs10923931 associated with troponin T levels in women, adjusted for glucose levels. These findings may indicate metabolic genetic influences on troponin T levels among women with psychosis. Highlights: Increased levels of hsTnT were found among patients with elevated fasting glucose. The above association remained significant also when adjusting for age and gender. hsTnT levels to genetic metabolic risk variants were tested in psychosis patients. hsTnT levels between genotypes of the rs10830963, and rs10923931 differ. hsTnT levels between genotypes differ only in women with psychosis.